Penilaian Kinerja Berbasis Value For Money dan Sistem Online Atas Penerimaan Pendapatan Asli Daerah Kabupaten Badung - Dewi, Ida Ayu Diah Kencana; Suartana, Wayan (E-Jurnal Akuntansi; Vol 22 No 2 (2018), 2018)
The purpose of this study is to know and analyze the performance of Regional Revenue Agency of Badung Regency in 2012 - 2016 in fulfilling the criteria of value for money, as well as whether there is a difference of revenue of the original revenue of Badung regency before and after using the local tax system online. Technique of collecting data of this research is interview and documentation. The type of data of this research is quantitative data covering the financial report data for the period of 2009 - 2016 and qualitative data which include historical data, vision of mission, and organization structure of Regional Revenue Agency of Badung Regency. Data analysis used in this research is comparative descriptive analysis related value for money and paired sample t-test. Bapenda performance of Badung Regency by using the concept of value for money is good, because it has met the criteria in terms of economy, efficiency and effectiveness. Bapenda performance of Badung Regency by using online system is categorized as good performance, it can be seen from result of paired sample t-test which produce significant value. Keywords: Performance measurement, value for money, online tax system area